ADOMA: A Command Line Tool to Modify ClustalW Multiple Alignment Output. Issue 1 (31st August 2015) - Zaal, Dionne; Nota, Benjamin
Abstract: We present ADOMA, a command line tool that produces alternative outputs from ClustalW multiple alignments of nucleotide or protein sequences. ADOMA can simplify the output of alignments by showing only the different residues between sequences, which is often desirable when only small differences such as single nucleotide polymorphisms are present (e.g., between different alleles). Another feature of ADOMA is that it can enhance the ClustalW output by coloring the residues in the alignment. This tool is easily integrated into automated Linux pipelines for next‐generation sequencing data analysis, and may be useful for researchers in a broad range of scientific disciplines including evolutionary biology and biomedical sciences. The source code is freely available at https://sourceforge. net/projects/adoma/. Abstract :